Wavelet analysis applied to CO2 fluxes in native grasslands of the Pampa biome under the influence of different ENSO phenomena - Silva, João Antonio Voltz da (2025)
The Brazilian Pampa biome is recognized for its extensive area dedicated to livestock farming, being one of the main producers of beef in the country. Greenhouse gas emissions or absorptions, such as CO2, are influenced by periods associated with ENSO phenomena (El Niño, EL and La Niña, LN). Continuous and Cross Wavelet transform analyses are effective methods for investigating differences in the gas exchanges, allowing the examination of temporal CO2 variability and the relationship with meteorological variables at different time scales. The meteorological and CO2 flux data used in this analysis were collected from a flux tower at the Santa Maria experimental site, with CO2 fluxes obtained using the Eddy Covariance technique. Wavelet analyses demonstrated the ability to identify flux patterns across different temporal scales, considering the influence of distinct phases of the ENSO in the Brazilian Pampa biome. The results indicate that the main differences between the EL and LN phenomena occur on a time scale between 16 to 32 days in the relationship of CO2 flux and Precipitation, being in spring for EL and summer/autumn in LN. The observed temporal patterns of CO2 fluxes and environmental variables highlight the importance of modeling CO2 flux concerning meteorological trends.